MMSET is dynamically regulated during cell-cycle progression and promotes normal DNA replication. Issue 1 (2nd January 2016) - Evans, Debra L.; Zhang, Haoxing; Ham, Hyoungjun; Pei, Huadong; Lee, SeungBaek; Kim, JungJin; Billadeau, Daniel D.; Lou, Zhenkun
ABSTRACT: The timely and precise duplication of cellular DNA is essential for maintaining genome integrity and is thus tightly-regulated. During mitosis and G1, the Origin Recognition Complex (ORC) binds to future replication origins, coordinating with multiple factors to load the minichromosome maintenance (MCM) complex onto future replication origins as part of the pre-replication complex (pre-RC). The pre-RC machinery, in turn, remains inactive until the subsequent S phase when it is required for replication fork formation, thereby initiating DNA replication. Multiple myeloma SET domain-containing protein (MMSET, a.k.a. WHSC1, NSD2) is a histone methyltransferase that is frequently overexpressed in aggressive cancers and is essential for normal human development. Several studies have suggested a role for MMSET in cell-cycle regulation; however, whether MMSET is itself regulated during cell-cycle progression has not been examined. In this study, we report that MMSET is degraded during S phase in a cullin-ring ligase 4-Cdt2 (CRL4 Cdt2 ) and proteasome-dependent manner. Notably, we also report defects in DNA replication and a decreased association of pre-RC factors with chromatin in MMSET-depleted cells. Taken together, our results suggest a dynamic regulation of MMSET levels throughout the cell cycle, and further characterize the role of MMSET in DNA replication and cell-cycle progression.